Penerapan Procedural Content Generation pada Pembangkit Level Gim Maze Heksagonal - Chyntia Savrila Putri; Eriq Muhammad Adams Jonemaro; Muhammad Aminul Akbar (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
A rapidly increasing demand of game content is the main reason which induced the urgency for a straightforward method for generating new level content that goes hand in hand with the automated technology field. A labyrin based level requires a certain uniqueness without the risk of encumbering the development process in time or budget. With that in mind, the author raises this thesis that proposes the use Binary Tree Algorithm to implement Procedural Content Generation to generate levels in a maze game genre. This algorithm will carve a maze path from two pre-determined directions, this implementation can result in a fast and simple generation. The result of this paper shows an average of 0.435 second to generate three levels with different sizes. The resulting levels are all valid and playable according to the labyrin parameters such as a valid starting and ending point, a path between these two points, and a labyrin that follows the set grid. This algorithm also has a bias for diagonal paths, and a long corridor is usually formed on two sides of the generated maze. The conclusion is that Binary Tree Algorithm is perfectly suitable as a maze level generator in a hexagonal grid with fast generating time and a reliable generated level.